Oral Tradition: The Role of Folklore in Preserving the Cultural Identity of Kumun Debai Subdistrict - Precillia, Monita (LPPM Institut Seni Indonesia Padangpanjang, 2024)
The Research on Preserving Cultural Heritage through Oral Tradition is of utmost importance, as the research represents an effort to maintain the cultural identity of the Kumun Debai District in the City of Sungai Penuh. The focus of the research is the role of folklore in preserving the oral tradition in the Kumun Debai District, through an in-depth understanding of proverbs, folktales, traditional songs, and other oral practices. The research aims to document, analyze, and comprehend the role of folklore in preserving the cultural heritage through oral tradition in the Kumun Debai District. This will help maintain the local cultural identity, prevent the loss of oral traditions, and ensure the preservation of local cultural values, which will be passed on to future generations. The study employs the theory of folklore in the context of preserving cultural heritage through oral tradition. The theory focuses on the in-depth understanding of proverbs, folktales, traditional songs, and other oral practices as an integral part of the cultural identity of a community. The use of the